Employee perception of managerial leadership power bases in the nationalised commercial banks of Bangladesh : an empirical study - Jahangir, Nadim; Haq, Mahmudul; Ahmed, Ezaz (© 2004 Journal of Business Administration, 2017)
This article was published in the Journal of Business Administration [ @ 2004 Journal of Business Administration. ]